1991
DOI: 10.1007/bf03174615
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive style and social behavior in young Mexican American children

Abstract: The relationship between 76 five-year-old Mexican American children's cognitive style and their sociability was explored in five kindergarten public school classrooms. The children's cognitive style, social competence, sociometric status, social role taking and social problem solving and social play were assessed. Main effects were found in the children's play behaviors, selection of play areas, perspective taking, social competence and sociometric nominations.L'auteur a explore la relation entre les styles co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This initially unexpected result relates to the fact that also different neurophysiological patterns have been identified for both behaviors in the current study. The above mentioned interpretation that instrumental helping relies on task-related decision making processes could also offer an explanation of the negative correlation between infants' understanding of others' distress and instrumental helping behavior as it has been suggested that task-orientation and social orientation form two different orientations of the same personality dimension (Nakamura and Fink, 1980;Saracho, 1991). In other words, our results could suggest that instrumental helping reflects task-orientation, whereas distress understanding is related to social orientation.…”
Section: Discussionmentioning
confidence: 55%
“…This initially unexpected result relates to the fact that also different neurophysiological patterns have been identified for both behaviors in the current study. The above mentioned interpretation that instrumental helping relies on task-related decision making processes could also offer an explanation of the negative correlation between infants' understanding of others' distress and instrumental helping behavior as it has been suggested that task-orientation and social orientation form two different orientations of the same personality dimension (Nakamura and Fink, 1980;Saracho, 1991). In other words, our results could suggest that instrumental helping reflects task-orientation, whereas distress understanding is related to social orientation.…”
Section: Discussionmentioning
confidence: 55%
“…We adopted this duration based upon existing literature (Howes & Matheson 1992;Saracho, 1991Saracho, , 1996. We also adopted the Howes and Matheson (1992) play scale that assessed the social aspects of children's play.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…We scored the individual pictures and then averaged them together for the creativity score (see Saracho, 1991Saracho, , 2002. Children's drawings received points for anatomical features and accessories that appeared on the body.…”
Section: Design and Proceduresmentioning
confidence: 99%